Deliverable 2.2 Report on exploitation of existing data: ocean and sea ice data - Sagen, Hanne; Hamre, Torill; Storheim, Espen; Yamakawa, Azuka; Dushaw, Brian; Sandven, Stein; Pirazzini, Roberta; Schewe, Ingo; Soltwedel, Thomas; Behrendt, Axel; Ludwigsen, Carsten Ankjær; Andersen, Ole B.; et al. (Zenodo, 2018)
This report presents a selection of data products from existing ocean and sea ice measurements under WP2 Task 2.2 (Exploitation of existing data towards improved data products). This is done by applying various methodologies for data processing to derive of geophysical and biogeochemical quantities that can be used for further work in the project, especially in WP5 (Data management and integration) and in WP6 (Applications towards stakeholders). This report is complementary to D2.1 (Report on present observing capacities and gaps: ocean and sea ice observing systems), which includes an assessment of existing data collections based on an on-line survey (https://intaros.nersc.no/node/651) . NERSC presents acoustic data from several field experiments in the Fram Strait carried out over a period of 110years. The presentation includes both active and passive acoustic data, description of how the experiments were conducted, processing steps from raw data to the resulting data products, and standardisation of formats for data and metadata. UiB and GEUS present an earthquake catalogue for the Arctic region (described in D2.8). AWI presents the Unified Database for Arctic and Subarctic hydrography (UDASH), which includes all available data for the period 1980-2015. This archive is updated yearly and is available from the PANGAEA repository. IOPAN presents a reprocessed hydrography data set for the Nordic Seas and the Fram Strait area collected by RV Oceania from 1988 to 2017 (the AREX programme). The data set is used for higher-level products such as time series of transports, heat content and dynamic topography. IOPAN also presents data from the A-TWAIN moorings north of Svalbard, deployed from 2012-2017. These data includes profiles of CTD and current data, which are used to present time series of temperature, salinity and currents. Furthermore, IOPAN presents Argo floats in the Nordic Seas and hydrographic data sets from Svalbard fjords. DTU Space presents satellite radar altimeter products from 26 years of data in ...